If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(y + -7) = 3(y + 2) Reorder the terms: 8(-7 + y) = 3(y + 2) (-7 * 8 + y * 8) = 3(y + 2) (-56 + 8y) = 3(y + 2) Reorder the terms: -56 + 8y = 3(2 + y) -56 + 8y = (2 * 3 + y * 3) -56 + 8y = (6 + 3y) Solving -56 + 8y = 6 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -56 + 8y + -3y = 6 + 3y + -3y Combine like terms: 8y + -3y = 5y -56 + 5y = 6 + 3y + -3y Combine like terms: 3y + -3y = 0 -56 + 5y = 6 + 0 -56 + 5y = 6 Add '56' to each side of the equation. -56 + 56 + 5y = 6 + 56 Combine like terms: -56 + 56 = 0 0 + 5y = 6 + 56 5y = 6 + 56 Combine like terms: 6 + 56 = 62 5y = 62 Divide each side by '5'. y = 12.4 Simplifying y = 12.4
| 6y=3x-4 | | 3x^3-14x^2+3x+36=0 | | l=2m | | 5+[30-(6-1)2]= | | 2.6=-0.9y | | 32x^2-1=0 | | 0.5f-2=0.166667 | | 8x+13=4x+77 | | 17g=11g | | =ax^4 | | 5(p+2)=15p+4 | | 7(90-x)=5x | | 6x+7=4a+7 | | (x+(x+8)+(10+(x+8)))=125 | | 100-3x=33x+24 | | 3x^2-3x+2=2x^2+x-1 | | 25r^2-25r+6=0 | | 20z+-3z+-13z=-20 | | -0.00512y+1.7787=12.007y-1.005 | | -0.00512y+1.7132=13.002y-1.008 | | -0.0512y+1.7132=13.002y-1.008 | | -0.00378y+1.6781=13.002y-1.008 | | (80-x)10=10 | | 89x+56=67 | | 17=5x+5y | | 50-90x=89 | | Cos(8x)+cos(4x)+2cos(2x)=0 | | 45-89x=-78 | | 2v+2u+5u= | | 79x-76=90 | | x^2+20x+4800=0 | | 78x+76=89 |